The Relationship Between Education, Knowledge and Parenting Patterns of Mothers Towards The Incidence of Wasting in Toddlers - Rosalina Madai; Nur Al-faida; Bau Kanang (International Journal of Public Health, 2024)
Background:Wasteis a condition of acute malnutrition where the weight of a toddler is not in accordance with his height and the z-score value <-2. Toddlerhood is an important life and needs to be considered by parents. Toddlers need to get nutrients from daily food in the right amount and good quality. Education, maternal knowledge affects children's food choices, good maternal parenting patterns, children will grow and develop well by coming to the integrated health post, monitoring toddler weight is a positive attitude in solving problems. Purpose: This study was to determine the level of education, knowledge and maternal parenting patterns on the incidence of wasting in the work area of ​​the Nabarua Health Center UPTD, Nabire Regency. Method: The research design used was Cross Sectional. The sample used was 30 toddlers using total sampling. Data analysis used the Statistical Program for Social Science (SPSS) Version 16.0 computer release program and used the chi-square test. Results: test of the relationship between maternal education (p value = 0.23), maternal knowledge (p-value = 0.43), and Parenting (p-value = 0.82). Conclusion: There is no relationship between maternal education, maternal knowledge, and maternal parenting patterns with wasting incidents. Suggestion: It is expected that mothers of toddlers provide daily food in the right amount and good quality, good maternal parenting patterns so that children grow and develop well by coming to the integrated health post to monitor their child's weight.